Exploring the relationship between variables for online learning motivation among undergraduates / Siti Aishah Taib, Norhisyam Jenal and Noor Hanim Rahmat - Taib, Siti Aishah; Jenal, Norhisyam; Rahmat, Noor Hanim (UiTM Press, 2024)
The absence of human face-to-face communication during the COVID-19 pandemic has raised the concern of online learning motivation among students due to the sudden emergency remote teaching and learning in Malaysia. The three aspects of learning motivation that are often studied in the field of education are value, expectancy, and affective components. Hence, this paper presents the relationship between the three variables for online learning motivation among undergraduates during the emergency remote teaching and learning period. A set of questionnaires comprising three sections and 24 items was employed in this quantitative study. The survey was conducted online to 151 respondents from a Malaysian public university, and the data collected were analysed using descriptive and inferential statistics. Findings indicated that online students provided positive responses for all the three components of online learning motivation: namely, value, expectancy, and affective. Meanwhile, correlations tests yielded a strong positive relationship between value and expectancy components and a weak positive relationship between value and affective components. This paper also discusses pedagogical implications and future research of the study.